Linguistic vitality of bahasa Malaysia in an integrated society - Abdullah, Ain Nadzimah; Chan, Swee Heng; Cheah, Mun Chun (Penerbit Universiti Pertahanan Nasional Malaysia, 2012)
Linguistic vitality can suggest forecast assessment of a broad range of language attitudes and language communicative behaviours (Sachdev & Bourhis, 2005). In a society, language vitality will reflect the dominance of languages in use. It is prudent to investigate the impinging factors to come to an understanding of societal needs and wants in terms of language use, both from the micro and macro societal viewpoints. A study of this nature is intrinsically complicated but essential in terms of understanding language use and its link to linguistic identity-setting within a culture. Malaysia, with its multi- ethnic environment yet encompassing a variety of ethno-linguistic groups is potentially a very rich source for research that makes important links between language and the emergence of linguistic identities. This study aims to measure the linguistic vitality of Bahasa Malaysia amongst Malaysian undergraduates to give indicators about its status of use. Data for the study were obtained by using questionnaires that helped illuminate the factors that affect the vitality of the language in Malaysian society.